Rapid Whole Genome Sequencing of Serotype K1 Hypervirulent Klebsiella pneumoniae from an Undocumented Chinese Migrant. (28th April 2021) - Macleod, C. K.; Khokhar, F. A.; Warne, B.; Wick, R.; Butcher, R.; Cassimon, B.; Hayden, P.; Holt, K.; Török, M. E.
Abstract : Background . Hypervirulent Klebsiella pneumoniae causes severe disseminated infections, typically with hepatic and central nervous system involvement including endophthalmitis. Case Presentation . We report a fatal case of an undocumented Chinese migrant in her 60s who presented to the emergency department with abdominal pain, lethargy, and headache over the preceding two weeks. She had a new diagnosis of diabetes mellitus on admission. Computed tomography scan of the thorax, abdomen, and pelvis showed bilateral pneumonia with liver abscesses. The patient was treated with empirical broad-spectrum antibiotics before K. pneumoniae was isolated from cerebrospinal fluid and blood cultures. The isolate was further characterised as a ST23 (ST: sequence type), serotype K1 hypervirulent strain using Nanopore sequencing. Despite admission to the intensive care unit, the patient died within 48 hrs of admission. Conclusions . This case demonstrates the need for increased awareness of hypervirulent K. pneumoniae, even in countries where it occurs infrequently. Novel, rapid, sequencing technologies can support diagnosis in unusual presentations.